Financial Support of Educational Institutions: Russian and Foreign Experience ("Journal "U". Economy. Management. Finance.", 2024)
The article is devoted to the issue of financing educational organizations in Russia and foreign countries. The article considers government spending on education as a percentage of GDP, as well as the ratio of state and non-state sources of education financing. Based on the results obtained, a conclusion is formulated about the global role of public finance for the development of education.
Keywords: economics; educational organizations; education expenses; sources of financing